Remote Laser-Induced Breakdown Spectroscopy of Bacterial Growths in Carbonate Rocks in a Mars-like Atmosphere - García-Gómez, Laura; Delgado-Pérez, Tomás; Fortes-Román, Francisco Javier; Del Rosal Padial, Yolanda Remedios; Liñán-Baena, Cristina; Fernández, Luis Efrén; Cabalín-Robles, Luisa María; Laserna-Vázquez, José Javier (Sage, 2023)
Understanding the past habitable environments of Mars increases the requirement to recognize and examine modern analogs and to evaluate the mechanisms that may preserve biosignatures in them. The phenomenon that originates and preserves possible microbial biosignatures in mineral phases is of particular interest in astrobiology. On Earth, the precipitation of carbonate matrices can be mediated by bacteria. Besides microbialites and other sedimentary structures, carbonate formations can be observed in certain karstic caves. The present work is focused on the remote laser-induced breakdown spectroscopy (LIBS) characterization of cyanobacteria, exploring the possibilities for identification and discrimination on carbonate substrates. For this purpose, the extremophile cyanobacterium Chroococcidiopsis sp. (collected from the Nerja Cave, Malaga, Spain) was analyzed under laboratory-simulated martian conditions in terms of chemical composition and gas pressure. LIBS results related to acquired molecular emission features allowed bacterial differentiation from the colonized mineral substrate. In addition, the limits of detection were estimated with a laboratory-grown culture of the cyanobacterium Microcystis aureginosa. Our results reveal LIBS's capability to detect biological traces under simulated martian conditions. Additionally, the time-resolved analysis of the biological samples demonstrates the selection of optimal temporal conditions as a critical parameter for the preferential acquisition of molecular species in organic material.
Keywords: Espectroscopía de plasma inducido por láser; Exobiología; LIBS; Cyanobacteria; Simulated Mars conditions; Biosignatures